Big hopes for small-scale fishers: a critical review of South Africa's small-scale fishing policy and regulations - Pretorius, Graeme (Institute of Marine and Environmental Law, 2017)
Some 18 years after the enactment of the Marine Living resources Act (18 of 1998), which gives express recognition to the subsistence or small-scale fisheries sector, a regime addressing the needs of this sector has finally been promulgated. That regime consists of the Policy for the Small Scale Fisheries Sector (20 June 2012) in South Africa and the Regulations relating to Small Scale Fishing (8 March 2016). Through a paradigm shift in small-scale fisheries governance, the regime seeks to put an end to the marginalisation and exclusion of these fishers from the fishing rights allocation process that has persisted in the absence of a formal regulatory regime. The Policy for the Small Scale Fisheries Sector purports to adopt and promote a human rights based approach and focuses on food security and livelihood. It seeks to employ co-management of the common pool resources and promote customary practices. It allocates a basket of multi-species rights to community legal entities allowing for a community based resource management with a strong developmental agenda. This paper seeks to reflect on the effectiveness of this regime by critically examining the regime governing the small scale fishing sector against the body of knowledge that has developed internationally regarding successful and effective management of the Small Scale fishing Sector.